1991
DOI: 10.1172/jci115286
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-mediated down-regulation of hepatic glutathione synthesis in the rat.

Abstract: Our present work characterized the role of hormone-mediated signal transduction pathways in regulating hepatic reduced glutathione (GSH) synthesis. Cholera toxin, dibutyryl cAMP (DBcAMP), and glucagon inhibited GSH synthesis in cultured hepatocytes by 25-43%. Cellular cAMP levels exhibited a lower threshold for stimulation of the GSH efflux than inhibition of its synthesis. The effect of DBcAMP was independent of the type of sulfur amino acid precursor and cellular ATP levels and unassociated with increased GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 36 publications
(47 reference statements)
4
55
1
1
Order By: Relevance
“…However, the ratio of GSH/GSSG levels was decreased by dexamethasone, suggesting that dexamethasone may impose oxidative stress in A549 epithelial cells. Depletion of liver GSH in mice and inhibition of GSH synthesis by dexamethasone have been observed in a rat hepatic cell line (50,51). Similarly, depletion of antioxidant enzyme activities have been shown in various rat tissues by glucocorticoid supplementation, and this depletion was more pronounced when rats were challenged with oxidative stress (52).…”
Section: Discussionmentioning
confidence: 89%
“…However, the ratio of GSH/GSSG levels was decreased by dexamethasone, suggesting that dexamethasone may impose oxidative stress in A549 epithelial cells. Depletion of liver GSH in mice and inhibition of GSH synthesis by dexamethasone have been observed in a rat hepatic cell line (50,51). Similarly, depletion of antioxidant enzyme activities have been shown in various rat tissues by glucocorticoid supplementation, and this depletion was more pronounced when rats were challenged with oxidative stress (52).…”
Section: Discussionmentioning
confidence: 89%
“…23,24) Glucagon and phenylephrine were found to depress the concentrations of GSH in hepatocytes by inhibition of an activity of gamma-glutamylcysteine synthetase, which is a key enzyme responsible for a rate-limiting step of the synthesis of GSH. 25 ) It has often been discussed how GSH metabolism may be associated with aging and diabetic complications. A negative correlation between GSH content and age was found in human bone marrow 26 ) and murine liver, kidney, and heart.…”
Section: Discussionmentioning
confidence: 99%
“…Various inflammatory agents such as cyclic adenosine monophosphate (cAMP) and intracellular calcium, which are released during inflammation, may inhibit GSH synthesis at the translational level (table 3) [107]. It has been shown that c-GCS activity is inhibited by agonists of various signal transduction pathways in rat hepatocytes [107], suggesting a role for signalling mechanisms in the TNF-a: tumour necrosis factor-a IL: interleukin.…”
Section: At Post-transcriptional and Translational Levelsmentioning
confidence: 99%
“…LU et al [107] reported that hepatic GSH synthesis is downregulated in response to hormones known to mediate their effects through the activation of distinct signal transduction pathways. Using various specific inhibitors of signalling pathways, these investigators determined that hormone-specific inhibition of GSH synthesis was mediated by the activation of protein kinase A, protein kinase C and Ca 2+ /calmodulindependent kinase II.…”
Section: At Post-transcriptional and Translational Levelsmentioning
confidence: 99%
See 1 more Smart Citation